Study on the Functions of Mihrab in the Selected Malaysian Mosques - Rosniza Othman (Journal of Architecture, Planning and Construction Management, 2020)
Mihrab and Qibla wall are two significant elements exist in any mosques. All aspects in designing the form of Mihrab on the Qibla wall should be taken into study so that the functions will not be misapprehended. Muslim world seizes Mihrab on the Qibla Wall of mosques as a space for Imam (the congregational leader). Archeological evidence confirmed on the existence of earliest Mihrab in the form of semi circular concaved niche used during the Umayyad Dynasty and then shape and form of Mihrab evolves throughout the centuries and across cultures. If the Mihrab is actually used for the Imam to lead the congregation, Mihrab should always remain within the same dimension according to normal human anthropometry in comfort and should fit a single prayer rug in the niche, regardless the size of mosque. The objective of the paper is mainly to observe the functions and usages of selected Malaysian Mosques Mihrabs. Typological analysis done reveals that the Mihrabs under study are sized and shaped differently. This concluded that the function of Mihrab in Malaysian mosques is not restricted to be an area for Imam leading the congregational prayers but it is more as an indicator of Qibla direction.